Pindar's songs for young athletes of Aigina - Burnett, Anne Pippin, 1925-2017 (OUP E-Books., 2005)
This book consists of individual studies of the poet Pindar's eleven odes for the victors of the athletic contests on the island of Aigina. Anne Pippin Burnett addresses questions of mythic self-presentation, as well as Pindar's techniques for unifying his audience and leading it into a shared experience of inspired success. - ;This book consists of individual studies of Pindar's eleven odes for Aiginetan Of the forty-six surviving victory odes of Pindar, eleven give praise to athletes from the island of Aigina in the Saronic Gulf. This book offers studies of those eleven songs, preceded by a brief survey of the island's history, a sketch of its peculiar aristocracy, and a description of the sculptural programme of its early fifth-century temple of Aphaia--because the author's concentration is always upon effects produced within the immediate audience when the odes were performed. As hosts or guests, members of a small commercial elite watched while dancers celebrated the athletic success of one of their own number, and the conditions of performance remained essentially unchanged from the 490s through the 460s BC, in spite of Aigina's gradual loss of power. The songs that Pindar supplied for these occasions invite a close consideration of the epinician mode, for all are ample in scale and complex in design, while at the same time all share a local awareness of the pediments of the Aphaia Temple and all (so it is argued) salute victors who are under 18 years of age. In addition, each performance displays a mythic marvel, and Anne Pippin Burnett argues that these segments of narrative are meant to bring a touch of performance to a worldly celebration, offering to the gathered masculine auditors imperishable proofs of their common identity. Burnett's overall concern is with Pindar's techniques for leading spectators into a shared experience of inspired success, but she is also alert to the historical realities of Greek athletic contest.--Book jacket., preceded by a brief survey of the history of the island and the nature of its aristocracy. Anne Pippin Burnett's discussion is particularly attentive to questions of mythic self-pres.